Wisconsin freshwater isopods (Asellidae) - (:unkn) unknown (My University, 1997)
Four species of freshwater isopods in the family Asellidae were collected from Wisconsin. There is very little published information on the asellid isopods of Wisconsin. In this paper we provide descriptions of the size range, habitat characteristics, distribution, and life history traits of Wisconsin asellids based on data from our field work and information from the literature. We include a provisional key for identification of the male asellids which have been collected from Wisconsin.
Keywords: freshwater isopods; Asellidae; Caecidotea